Hubungan Manajemen Diri Dengan Kadar Gula Darah Puasa Pada Penderita Diabetes Melitus Tipe 2 Di Puskesmas Andalas Kota Padang - Ria Desnita; Mira Andika; Fitria Alisa; Zulham Efendi; Weny Amelia; Lola Despitasari; Defrima Oka Surya; Vivi Syofia Sapardi (JURNAL KESEHATAN MERCUSUAR, 2023)
Diabetes Mellitus (DM) type 2 is a metabolic disorder characterized by hyperglycemia or high blood sugar levels and impaired carbohydrate, protein and fat metabolism caused by insulin resistance. One of the factors that influence the control of fasting blood sugar levels is self-management. The purpose of this study was to determine the relationship between self-management and fasting blood sugar in patients with type 2 diabetes mellitus at the Andalas Public Health Center, Padang City. This research is a descriptive correlational study with a cross sectional approach, carried out in January-August 2022 at the Andalas Health Center, Padang City. The number of samples is 44 people with the Accidental Sampling method. Univariate analysis is shown in the frequency distribution table and bivariate with Spearman's test. The results of this study showed that 50% of respondents had poor self-management. The average fasting blood sugar level was 197 mg/dl with a standard deviation of 61.3 mg/dl. There is a relationship between self-management and fasting blood sugar levels in patients with type 2 diabetes mellitus at Andalas Public Health Center, Padang City with p value = 0.000.. It is recommended to health workers to make self-management as one of the nursing interventions in controlling fasting blood sugar levels in patients with type 2 diabetes mellitus.